ELECTRONIC STRUCTURE AND SEMICONDUCTOR TO FERROMAGNETIC PHASE TRANSITION IN FeAs WITH TETRAHEDRAL BOND - Cabrera Arista, César (2025)
Here the electronic structure and the total energy of the FeAs alloy with a zinc blende-type crystal lattice were calculated. The LMTO method, an effective LDA-type potential that uses the exchange and correlation approximation of a homogeneous electron gas of polarized spin to solve the Schrödinger equation of the crystal lattice, were used. The energy bands, state density, and total energy of the FeAs were calculated for seven different cases of a small fraction of the valence electron charge centered on the empty spheres of the diagonal in the lattice. A band structure with a gap of 2,72 eV associated with a semi-stable semiconductor phase and with a total energy of −17,59 Ry was obtained. A stable ferromagnetic phase of FeAs was also obtained with an electronic structure that presents two peaks spaced by 354 meV near the Fermi energy, with a minimum total energy of -19,68 Ry. A result that can well be associated with a spin splitting of electronic states, already observed in experimental studies.